2019
DOI: 10.1002/cncr.31790
|View full text |Cite
|
Sign up to set email alerts
|

The role of neuro‐immune interactions in cancer‐related fatigue: Biobehavioral risk factors and mechanisms

Abstract: Fatigue is a common and distressing symptom in both patients with cancer and cancer survivors. There is substantial variation in the severity and persistence of cancer‐related fatigue that may be driven by individual differences in host factors, including characteristics that predate the cancer experience as well as responses to cancer and its treatment. This review examines biobehavioral risk factors linked to fatigue and the mechanisms through which they influence fatigue across the cancer continuum, with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
120
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(143 citation statements)
references
References 128 publications
(246 reference statements)
5
120
0
9
Order By: Relevance
“…In particular, IL-1 is of great interest because of its important role in congenital immune system and other physiological systems. Studies reported the role of two of the 11 members belonging to the IL-1 family, including IL-1α and IL-1β in fatigue [ 39 , 40 , 41 ] In this study, we have shown that 8-week FPP supplementation improves the level of IL-1β. Therefore, it is suggested that the anti-fatigue effect of FPP is mediated via regulation of inflammation, and the anti-fatigue effects result via downregulation of metabolite accumulation in exercise-induced fatigue.…”
Section: Discussionsupporting
confidence: 51%
“…In particular, IL-1 is of great interest because of its important role in congenital immune system and other physiological systems. Studies reported the role of two of the 11 members belonging to the IL-1 family, including IL-1α and IL-1β in fatigue [ 39 , 40 , 41 ] In this study, we have shown that 8-week FPP supplementation improves the level of IL-1β. Therefore, it is suggested that the anti-fatigue effect of FPP is mediated via regulation of inflammation, and the anti-fatigue effects result via downregulation of metabolite accumulation in exercise-induced fatigue.…”
Section: Discussionsupporting
confidence: 51%
“…This would help to disentangle the specificity of the link between adverse emotional experiences and fatigue as an MS-related or a more general phenomenon. A link between adverse emotional experiences and fatigue has also been reported in other medical conditions, such as CFS or cancer (40,41).…”
Section: Discussionmentioning
confidence: 77%
“…Reduced locomotion may be indicative of fatigue in mice, another common side effect of chemotherapy, although further analyses to assess fatigue are necessary. Each of these sickness behaviors is associated with peripheral inflammation in chemotherapy patients 44,45 and other rodent models 46 . Indeed, in the present study, paclitaxel-treated mice demonstrated evidence of peripheral inflammation including increased spleen mass in conjunction with increased transient concentrations of circulating LBP, IL-1β, TNFα, and CXCL1.…”
Section: Discussionmentioning
confidence: 99%